Elevação da gama-glutamiltransferase sérica na hepatopatia esquistossomótica não se correlaciona com a carga parasitária e precede alterações ultra-sonográficas - Ana Cristina de Castro Amaral Feldner; Luciane Aparecida Köpke de Aguiar; Mônica Rodrigues de Araújo Souza; Carlos Fischer de Toledo; Durval Rosa Borges (2002)
Liver disorders are the major manifestations of schistosomiasis mansoni. Factors that account for increased concentrations of cholestasis-indicating enzymes in the hepatosplenic form of the disease are unknown.To assess the correlation between increased gamma-glutamyltransferase serum levels and both the parasitic load and ultrasound alterations in patients with schistosomiasis.Twenty-five patients with the chronic form of schistosomiasis were assessed for the presence or absence of increased enzymatic levels, for the parasitic load (low x medium/high) and for ultrasound parameters. Furthermore, analysis of prothrombin time and a platelet count were performed.Of the 25 patients, 13 showed increased gamma-glutamyltransferase plasma levels. No significant correlation was found between increased gamma-glutamyltransferase levels and the parasitic load, or between increased enzyme levels and ultrasound alterations. Nor did the prothrombin index or the platelet count differ between the two groups (normal gamma-glutamyltransferase levels and increased gamma-glutamyltransferase levels).The parasitic load explains no rise in gamma-glutamyltransferase plasma levels in patients with the chronic form of schistosomiasis, and conventional ultrasound is not a sensitive method to detect the alteration suggested by the increased enzyme level in those patients.